The longevity of habitable planets and the development of intelligent life. Issue 3 (30th August 2016) - Simpson, Fergus
Abstract: Why did the emergence of our species require a timescale similar to the entire habitable period of our planet? Our late appearance has previously been interpreted by Carter (2008) as evidence that observers typically require a very long development time, implying that intelligent life is a rare occurrence. Here we present an alternative explanation, which simply asserts that many planets possess brief periods of habitability. We also propose that the rate-limiting step for the formation of observers is the enlargement of species from an initially microbial state. In this scenario, the development of intelligent life is a slow but almost inevitable process, greatly enhancing the prospects of future search for extra-terrestrial intelligence (SETI) experiments such as the Breakthrough Listen project.